长江源多年冻土区季节性河流氢、氧同位素组成 - 刘光生; 王根绪; 高洋; 赵超 (2015)
Frozen soil plays a key role in hydrological processes and their observations are rare and difficult in permafrost regions. The stable hydrogen and oxygen isotope methods provide a useful tool for permafrost hydrology research. In this study, stable hydrogen and oxygen isotopes composition in seasonal river water was analyzed based on the stable isotope ratios (8D and delta~(18)O) data in precipitation and river water in a permafrost watershed in Yangtze River headwater region in 2009, combined with meteorological and hydrological data. The results showed that the delta~(18)O, 8D and the excess deuterium variation of river water and rainfall all presented descending trends during research period. This implies that the precipitation is the most important source of river water. The 8D in river water in the 2nd and 3rd sub-basin were -66.8%o and -69.6%o, respectively ,which were similar to the 8D in precipitation (-66.7%o). However, the 8D in river water in the 5th sub-basin (62.4%o) was significantly higher than that in precipitation. Higher vegetation coverage in the 5th sub-basin,higher soil organic matter content,soil moisture and actual evapotranspiration and strong evaporation fractionation effect enriched river water in the 5 th sub-basin with heavy isotopes. In June,as the soil melt down,frozen soil water of heavy isotope (8D, -71.3%。) was displaced by precipitation (deltaD, -12.1%o) and then fed the river water. In October, the frozen soil inhibited precipitation infiltration and made hydrogen isotope change quickly with precipitation. These indicate that the freeze-thaw cycle plays an important role in runoff processes in the permafrost regions. This study provides isotopic evidence in hydrological cycle research and a theoretical support of water resource protection in permafrost regions.